Disney Frozen. The Christmas party - Posner-Sanchez, Andrea; Disney Storybook Artists (New York : Random House, 2014)
Describes how Anna, Elsa, and the rest of the Arendelle celebrate Christmas.
At head of title: Disney Frozen.
AD 340
Keywords: Sisters -- Juvenile fiction; Princesses -- Juvenile fiction; Christmas stories